Adora2A downregulation promotes caffeine neuroprotective effect against LPS-induced neuroinflammation in the hippocampus - Lemes dos Santos Sanna, Paula; Bernardes Carvalho, Liebert; Cristina dos Santos Afonso, Camila; de Carvalho, Kassia; Aires, Rogério; Souza, Jennyffer; Rodrigues Ferreira, Marcel [UNESP]; Birbrair, Alexander; Martha Bernardi, Maria; Latini, Alexandra; Foganholi da Silva, Rodrigo A. (Elsevier, 2024)
Caffeine has been extensively studied in the context of CNS pathologies as many researchers have shown that consuming it reduces pro-inflammatory biomarkers, potentially delaying the progression of neurodegenerative pathologies. Several lines of evidence suggest that adenosine receptors, especially A1 and A2A receptors, are the main targets of its neuroprotective action. We found that caffeine pretreatment 15 min before LPS administration reduced the expression of Il1b in the hippocampus and striatum. The harmful modulation of caffeine-induced inflammatory response involved the downregulation of the expression of A2A receptors, especially in the hippocampus. Caffeine treatment alone promoted the downregulation of the adenosinergic receptor Adora2A; however, this promotion effect was reversed by LPS. Although administering caffeine increased the expression of the enzymes DNA methyltransferases 1 and 3A and decreased the expression of the demethylase enzyme Tet1, this effect was reversed by LPS in the hippocampus of mice that were administered Caffeine + LPS, relative to the basal condition; no significant differences were observed in the methylation status of the promoter regions of adenosine receptors. Finally, the bioinformatics analysis of the expanded network demonstrated the following results: the Adora2B gene connects the extended networks of the adenosine receptors Adora1 and Adora2A; the Mapk3 and Esr1 genes connect the extended Adora1 network; the Mapk4 and Arrb2 genes connect the extended Adora2A network with the extended network of the proinflammatory cytokine Il1β. These results indicated that the anti-inflammatory effects of acute caffeine administration in the hippocampus may be mediated by a complex network of interdependencies between the Adora2B and Adora2A genes.
Keywords: Adenosine receptors; Bioinformatics analyses; Cytokines; Inflammasome; Neuroinflammation